Exploring The Controversy Over School Accreditation Standards In Shaping Public Perceptions Of National Education Quality - Sutriani; Mohamed Nor, Abdullah Shukri (The Faculty of Education and Teaching Training, 2024)
This study examines the controversy of school accreditation standards in shaping public perceptions of the quality of national education at SMA Al-Hikmah Muncar Banyuwangi. This research uses qualitative methods, with data collection through observation, interviews and documentation. Data analysis used three model analysis techniques. The results show that there is a diversity of community perceptions of accreditation, which is influenced by various factors such as personal experience, socio-economic background and information obtained. In addition, three points emerged relating to the accreditation process at Al-Hikmah Muncar Banyuwangi High School, namely a too narrow focus on administrative aspects, lack of transparency, and limited stakeholder involvement. To improve the quality of education, this study suggests the need for a more comprehensive evaluation of the accreditation system.